A Facile Four-component Synthesis of Pyrazolophthalazines Using Tetrabutylammonium Bromide as Efficient Ionic Liquid Catalyst - Issazadeh, Zahra; Brazandehdoust, Maryam; Mamaghania, Manouchehr (International Pharmacy Acta, 2018)
An efficient method for the synthesis of pyrazolophthalazine derivatives was developed by using tetrabutylammonium bromide (TBAB) as ionic liquid catalyst in excellent yields (88-95%). Introduction: Most of the significant advances against disease have been made by designing and testing new structures, which are often heteroaromatic derivatives. In addition, over 80% of the top small molecule drugs by U.S. retail sales in 2010 contain at least one heterocyclic fragment in their structure. Therefore, researchers are on a continuous pursuit to design and produce better pharmaceuticals, pesticides, insecticides, rodenticides, and weed killers by following natural models. A significant part of such biologically active compounds is composed of heterocycles [1]. Moreover, phthalazine derivatives possess a versatile pharmacological properties including anticonvulsant, vasorelaxant, and cardiotonic activities. Methods and Results: We report here an efficient method for the synthesis of pyrazolophthalazine derivatives by a four-component reaction of equimolar amounts of phthalic anhydride, hydrazine hydrate, arylaldehydes and malononitrile in the presence of 20 mol tetrabutylammonium bromide (TBAB) ionic liquid as catalyst, in excellent yields. Conclusions: The protocol described here produced the desired pyrazolophthalazines in excellent yields (88-95%) and lower reaction times. The catalyst was reused at least 5 times without appreciable reduction in catalytic activities.